The Evaluation and Comparison of Removable Dentures Constructed with The SR-IVOCAP System and The Traditional System.: Life Sciences -Dentistry - Xhajanka, Prof. Edit; Hysenaj, Dr. Neada; Dr. Vergjini Mulo, Prof.; Mele, Dr. Dorina; Tedi Verçani, Dr.; Endrit Paparisto, Dr. (International Journal of Life Science and Pharma Research, 2023)
The treatment of edentulous patients is still a challenging problem. Acrylic resin is the most used material forconstructing removable denture bases. The main disadvantage of this material is resin shrinkage, which occurs during and afterpolymerization. Our study aimed to evaluate the denture parameters regarding patient satisfaction regarding the removabledentures constructed with two different processing techniques: compression molding and injection. 80 patients, who came in theUniversity Dental Clinic, Tirana were examined and evaluated. Those who fulfilled the criteria were treated with removabledentures. The patients were divided into two groups: in the first group, 40 patients were treated with removable denturesconstructed with the compression molding technique, and in the second group, 40 patients were treated with removable denturesconstructed with the injection molding technique. All the clinical and laboratory procedures until the processing technique wereidentical. After denture delivery, all the patients were re-scheduled to fulfill a questionnaire regarding four parameters of theremovable dentures: denture stability, mastication efficiency, denture comfort, and quality of dentures in general. Results. Thedescriptive statistics of the data were done. Sample t-test showed that the SR IVOCAP dentures had higher mean values for allthe parameters than the traditional dentures. Based on our study, the satisfaction of the patients treated with removable dentureswith the SR-IVOCAP system for all the parameters evaluated was higher compared to the patient satisfaction treated withtraditional removable dentures.